Prevalence and molecular characterization of Raillietina tapeworms in house crows: implications for public health - Wajid Ali Shah; Sumaira Shams; Wali Khan; Patricio De los Rios-Escalante; Nasib Khan; Mansoor Ahmad; Mashael Abdullah Aldamigh (Cogent Food & Agriculture, 2025)
Widely distributed house crows act as scavengers. This study investigated the prevalence and molecular characterization of potentially zoonotic Raillietina tapeworms. House crows were captured using mist nets. Tapeworms were preserved in 70% ethanol (−20°C) and identified morphologically and molecularly. DNA was extracted using phenol-chloroform; 18S rDNA was amplified by PCR and visualized after gel electrophoresis. Logistic regression analyzed prevalence factors; chi-square tested associations between categorical variables and infection. Raillietina infected 47.22% of crows, with prevalence differing by sex, age, health, area, and month. Females had higher infection rates (60%) than males (31.2%) (OR = 5.00, CI: 1.25–22.70, p > .05; p > .05). Subadults (76.9%) were more susceptible than adults (30.4%), (OR = 0.81, CI = 0.19–3.23, p > .05; p < .05). Weak crows (63.6%) showed higher susceptibility compared to healthy ones (32%), (OR = 4.88, CI = 1.00–36.42, p > .05; p > .05). Urban crows showed significantly higher infection rates (55.5%) than rural crows (38.8%) (OR = 0.0481, CI = −5.119 to −1.405, p < .05; p > .05). Compared to colder months, prevalence was found higher during summer months, highest in June and August (OR = 2.073, CI = 0.7396–8.519, p < .05; p < .05). The study highlights zoonotic Raillietina prevalence and molecular identification, recommending future research on crow-human transmission pathways.